1980
DOI: 10.1002/jrs.1250090604
|View full text |Cite
|
Sign up to set email alerts
|

Redetermination of some of the spectroscopic constants of the electronic ground state of di‐Nitrogen 14N2, 14N15N and 15N2 using coherent anti‐stokes Raman spectroscopy

Abstract: Calibrated coherent anti-Stokes Raman (CARS) spectra have been recorded for the resolved Q branches of the vibrational fundamentals and first hot bands of I4N,, l4N''N and 15N, at a temperature of 1200 K. The spectra show a convolved linewidth of 0.13 cm-', and have been used to derive new values of spectroscopic constants, for the species observed, with specific reference to the position of the Q branch lines where J > 20 for u = 1-0, and J = 0-30 for u = 2-1. The critical overlap region of the fundamental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…(22), rather than the constrained parameters implied by Dunham's with differences deduced from the only other Raman data, from measurements of Q branches by Bendtsen (5) and by notation (23,24). In the latter case, for example, one conGilson et al (6) (3,8,9,11) for 14 N 2 terms D 10 and D 20 were found to be statistically significant are hindered by the variation in number of fitted parameters and are listed in Table 3. Compared to the two separate fits, in the various fits; in general the major Y kl values are consis-the combined analysis decreased the number of parameters tent but our decreased estimated standard errors imply much from 18 to 12, the values of which can be used for the increased precision.…”
Section: Coefficients Y Kl and U Klmentioning
confidence: 87%
See 2 more Smart Citations
“…(22), rather than the constrained parameters implied by Dunham's with differences deduced from the only other Raman data, from measurements of Q branches by Bendtsen (5) and by notation (23,24). In the latter case, for example, one conGilson et al (6) (3,8,9,11) for 14 N 2 terms D 10 and D 20 were found to be statistically significant are hindered by the variation in number of fitted parameters and are listed in Table 3. Compared to the two separate fits, in the various fits; in general the major Y kl values are consis-the combined analysis decreased the number of parameters tent but our decreased estimated standard errors imply much from 18 to 12, the values of which can be used for the increased precision.…”
Section: Coefficients Y Kl and U Klmentioning
confidence: 87%
“…The Q-branch vacuum wavenumber input data sets and uncertainties specified above. The deduced parameters were R e and coefficients c j , 0 £ j £ 6 values of Tables 1 and 2 Table 3; experimental values are taken from this work, from Gilson et al (6), and from Bendtsen ( 5). Numbers in parentheses indicate the range of J for each Q branch.…”
Section: Potential-energy Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…1) even for measurements at high pressures. 2,3 For this, also the spectroscopic constants of N 2 have been determined accurately 4,5 and the collisional parameters of N 2 have been studied extensively (see, e.g., . Nevertheless, there are applications such as oxygen-fuelled combustion in which N 2 is not present to a significant extent.…”
Section: Introductionmentioning
confidence: 99%
“…6 In Ref. 2, the CARS spectra of the fundamental and first hot bands of nitrogen were employed to redetermine some constants. Two studies have been devoted to the u = 0 -+ 1 transition by using a highaccuracy absolute wavenumber calibration with the help of stimulated Raman3 or quadrupolar absorption6 spectroscopy.…”
Section: Introductionmentioning
confidence: 99%